Solitary cecal diverticulum: acute complication - Gateño Yaffe, Nisso (Cirugía del Uruguay, 1973)
Consideration of one case of isolated caecal diverticulitis includes discussion of peroperatory semiological. manouvres for the purpose of diagnosis and adequate treatment of this benign disease.